Barometer Pembagian Wasiat Wajibah Bagi Anak Angkat: Realisasi Keadilan, Analisis Perkara No. 1914/Pdt. G/2018. PA. Pbr - Hafiz, Muhammad; Nelli, Jumni; Nurul Islam, Adikza (UIN Sunan Kalijaga, 2023)
Adopted children are not part of the group of heirs who are entitled to inherit from the testator's estate. However, in an effort to create justice, the Compilation of Islamic Law (KHI) stipulates that adopted children are entitled to receive inheritance from the testator through the mandatory will (wasiat wajibah) mechanism with the condition that it cannot exceed 1/3 (one-third). This article examines the disparity in the decision of the Pekanbaru Religious Court No. 1266/Pdt. G/2018/ PA. Pbr which determines the adopted child's share of 1/8 (one - eighth) and decision No. 1869 /Pdt.G./ 2018/ PA. Pbr which determines that adopted children get 1/3 (one - third) of the heir's estate. Using a juridical-normative approach, this article finds that the difference in the amount of inheritance obtained by adopted children in the two decisions is at least caused by two things, namely (1) the absence of a definite amount stipulated in the law (KHI only mentions